Le non-recours à la formation continue en entreprise - Emmanuel de Lescure (La Nouvelle Revue du Travail)
This article seeks to show that, although the notion of non-take up was developed in the context of the fight against poverty, it is relevant for understanding the relationship of employees to in-company training. While successive reforms of training law have tended to make it an individual right, it is still not uniformly perceived as a universal good. By offering an initial measure of the phenomenon, the article shows that it concerns a significant proportion of the population and identifies a variety of contrasting and heterogeneous profiles whose relationship to training is studied. In doing so, it leads to the consideration of an element that is left in the shadows, the existence of a “non-demand” for training that distinguishes certain profiles.